Regulation, modification, and evolution of remote sign language interpreting in Sweden - a service in progress - Camilla Warnicke; Marie Matérne (BMC, 2024)
Abstract Background The sign language interpreting service has undergone a tremendous change due to COVID-19 and remote interpreting has become a more frequent alternative to the face-to-face format. The aim of the study is to investigate how the interpreters perceive the organisation of remote interpreting in Sweden and how it has evolved since the COVID-19 pandemic. Method Interviews with 26 experienced remote interpreters, representing 19 of Sweden's 21 counties, were analysed with qualitative content analysis. Results Three themes were revealed in the analysis. The first theme was regulation. It was stated that directives and regulatory decisions concerning provision of remote interpreting services were varied and unclear. Several different platforms were used when interpreting remotely. Some of the services had conducted risk analyses, whereas others had not. The second theme was modification, including adjusting interactions to suit the preferences and capabilities of the users (both signing and speaking parties), as well as adjustments to work environments and workplaces. The third theme, evolution of remote interpreting, showed that support and training were rare and varied. Although the processes and organisation of remote interpreting are not yet fully established in Sweden, remote interpreting is here to stay. Conclusions In Sweden, remote interpreting is a service that varies according to regulations and the type of assignments. The service would benefit from being more uniform and streamlined across Sweden, although consideration must be given to those involved with the service.